Social support as a mediator of the relationship between forgiveness and post-traumatic growth in hemodialysis patients: A structural equation modeling approach - Ye, Yansheng; Tong, Zongwu; Li, Changqiong; Gao, Xiufang; Sun, Yane; Xu, Jianqing; Xu, Qian; Song, Chengrong (Frontiers in Psychiatry, 2022)
Background Post-traumatic growth (PTG) refers to the positive psychological changes experienced with individuals after struggling with highly challenging life circumstances. Forgiveness can facilitate positive outcomes such as reduced distress, anxiety, and depression. Many studies have tested the relationships among forgiveness, social support, and PTG; however, a mechanism of social support has not been completely explored in hemodialysis patients. Objective To test the relationship between forgiveness and post-traumatic growth and verify the mediating factor of social support on the relationship between forgiveness and PTG in hemodialysis patients. Materials and methods In a descriptive cross-sectional study using convenience sampling from March to May 2021, 497 hemodialysis patients from nine hospitals filled out the Perceived Social Support Scale (PSSS), Heartland Forgiveness Scale (HFS), Post-traumatic Growth Inventory (PTGI), and general information. Data were analyzed using SPSS, and structural equation modeling was used to explore the relationships among forgiveness, social support, and PTG. Results Forgiveness was significantly positively associated with PTG (P < 0.01). The proposed model provided a good fit to the data. Social support was found to play a partial mediating role between forgiveness and PTG (a*b = 0.122, BCa 95% CI: 0.078∼0.181). Conclusion The results imply that forgiveness significantly directly and indirectly is related to PTG. Forgiveness in hemodialysis patients should be detected and effectively managed to ameliorate positive effects on PTG. It is necessary for nurses to consider implementing forgiveness interventions with an emphasis on building social support strategies to help hemodialysis patients enhance their PTG.